Corruption perception index: investor and Malaysia / Nor Amira Mohd Ali and Muhammad Hanif Abdul Gafar - Mohd Ali, Nor Amira; Abdul Gafar, Muhammad Hanif (Universiti Teknologi MARA, Kedah, 2023)
In this subtle and complex environment, fighting corruption, promoting transparency, and strengthening the country are critical to avoid further conflict and maintain peace in a new paradigm of globalization. As international businesspeople, they will face more complex tasks as compared to doing domestically. They should obey the laws not only of their home country but also the laws of the host countries in which it operates. Both home country and host country laws can effectively affect how international firms conduct business. One of the important parts of any business decision is to assess the political environment in which a firm operates. Many firms will be assessing the political climate in their home country conveniently. But assessing the political climates in other countries is more challenging and problematic. Ricky and Michael (2020) mentioned that political risk is any changes in the political environment that may adversely affect the value of a firm’s business activities. Thus, any activity which has the potential to harm a business's performance will be considered a risk to the business’s growth. Corruption is one of the political environment actors which has a significant effect on business performance. To measure whether the country is corrupt, it can derive and read from the Transparency International Corruption Perception Index (CPI), which is used as a proxy for assessing the level of government corruption for each economy (World Economics, 2021). The index is based on a scale of 0 to 100, where 0 is absolute corruption, and 100 is no perception of government corruption. In other words, CPI is also an important indicator of a country’s economic stability and growth potential, and whether it can attract more investors.